Hoot - Hiaasen, Carl. (New York : Yearling, 2005)
Roy, who is new to his small Florida community, becomes involved in another boy's attempt to save a colony of burrowing owls from a proposed construction site.
"A Yearling book."
Newbery Medal/Honor
Wilson's Children
Wilson's Junior High School
Book Links (A.L.A.), October 2009
Booklist, October 2002
Keywords: Burrowing owl -- Juvenile fiction; Environmental protection -- Juvenile fiction; Burrowing owl -- Fiction; Environmental protection -- Fiction; Owls -- Fiction; Burrowing owls -- Fiction; Environmental protection -- Fiction; Owls -- Fiction; Florida -- Juvenile fiction; Florida -- Fiction; Florida -- Fiction